Intervertebral disc internal deformation measured by displacements under applied loading with MRI at 3T. Issue 3 (6th May 2013) - Chan, Deva D.; Neu, Corey P.
<x xml:space="preserve">Abstract</x> Purpose Noninvasive assessment of tissue mechanical behavior could enable insights into tissue function in healthy and diseased conditions and permit the development of effective tissue repair treatments. Measurement of displacements under applied loading with MRI (dualMRI) has the potential for such biomechanical characterization on a clinical MRI system. Methods dualMRI was translated from high‐field research systems to a 3T clinical system. Precision was calculated using repeated tests of a silicone phantom. dualMRI was demonstrated by visualizing displacements and strains in an intervertebral disc and compared to T2 measured during cyclic loading. Results The displacement and strain precisions were 24 µm and 0.3% strain, respectively, under the imaging parameters used in this study. Displacements and strains were measured within the intervertebral disc, but no correlations were found with the T2 values. Conclusion The translation of dualMRI to a 3T system unveils the potential for in vivo studies in a myriad of tissue and organ systems. Because of the importance of mechanical behavior to the function of a variety of tissues, it's expected that dualMRI implemented on a clinical system will be a powerful tool in assessing the interlinked roles of structure, mechanics, and function in both healthy and diseased tissues. Magn Reson Med 71:1231–1237, 2014. © 2013 Wiley Periodicals, Inc.